Highly corrosion-resistant martensitic stainless steel and its manufacturing method
A martensitic stainless steel with controlled alloy composition and batch annealing process addresses the balance of corrosion resistance and hardness, enhancing workability and corrosion resistance for Western tableware applications.
Patent Information
- Application Number
- JP2022554348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-20
- Filing Date
- 2020-10-14
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-10-14
AI Technical Summary
Martensitic stainless steel used for cutlery faces challenges in achieving a balance between high corrosion resistance and hardness, with excessive carbon and chromium content leading to impaired workability and surface defects during polishing, and high precipitation temperatures of chromium carbides affecting corrosion resistance.
A martensitic stainless steel with controlled alloy composition (C: 0.14-0.21%, N: 0.05-0.11%, Si: 0.1-0.6%, Mn: 0.4-1.2%, Cr: 14.0-17.0%, C+N: 0.2-0.32%) and a batch annealing process that uniformly distributes fine chromium carbides and nitrides, ensuring a precipitation temperature of 950°C or less, followed by strengthening heat treatment to enhance corrosion resistance and hardness.
The solution results in a martensitic stainless steel with improved workability, corrosion resistance, and appropriate hardness suitable for Western tableware, with a Rockwell hardness of 47-53 HRC and a pitting potential of 180 mV or more, while minimizing energy costs and equipment limitations.
Smart Images

Figure 0007617937000004 
Figure 0007617937000005 
Figure 0007617937000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly corrosion-resistant martensitic stainless steel and a manufacturing method thereof, and more particularly to a highly corrosion-resistant martensitic stainless steel that can be used as a material for Western-style tableware and a manufacturing method thereof. [Background technology]
[0002] Materials for blades, such as kitchen knives, scissors, razors, and scalpels, which are commonly used medical instruments, require high hardness to maintain cutting ability and wear resistance, and also require excellent corrosion resistance because they are easily exposed to moisture or stored in a moist atmosphere. For this reason, high-carbon martensitic stainless steels with high hardness are mainly used as materials for blades. Blade materials are very brittle because they require high hardness. Therefore, they need to be softened to a certain level to make them easier to process. For this reason, they are manufactured using a batch annealing furnace (BAF) or high-temperature continuous annealing process, which makes heat treatment of brittle materials easy.
[0003] During annealing, chromium carbides, which are formed by the reaction of carbon and chromium, are dispersed and precipitated as fine particles in the ferrite matrix, which reduces the amount of dissolved carbon in the matrix, facilitating the application of stainless steel manufacturing processes such as rolling and pickling. In addition, the fine chromium carbides uniformly distributed in the ferrite matrix enable rapid re-dissolution of chromium and carbon into the high-temperature austenite phase during the strengthening heat treatment process performed by the final cutlery manufacturer, improving the hardness and corrosion resistance of the martensite structure after quenching. However, if the amount of carbon, nitrogen and chromium is increased to a certain level in order to improve the hardness and corrosion resistance of martensitic stainless steel for cutlery, the hardness will be excessively high, which will cause problems of poor workability and surface defects in the polishing process for gloss.The precipitation temperature of chromium carbide will increase, which will lead to problems of increased strengthening heat treatment temperature and problems of residual chromium carbide, which may result in poor corrosion resistance.
[0004] Therefore, in order to obtain martensitic stainless steel with excellent corrosion resistance and hardness suitable for polishing work, it is necessary to develop a steel material and establish an annealing pattern that can appropriately control the precipitation temperature of chromium carbide so that the chromium carbide is easily decomposed at the strengthening heat treatment temperature and that has a uniform distribution of fine chromium carbide. Summary of the Invention [Problem to be solved by the invention]
[0005] In order to solve the above problems, the present invention aims to provide a martensitic stainless steel hot-rolled annealed steel sheet having improved corrosion resistance by uniformly distributing fine chromium carbonitrides in the matrix structure and having appropriate hardness when subjected to strengthening heat treatment, a highly corrosion-resistant martensitic stainless steel using the same, and a manufacturing method thereof. [Means for solving the problem]
[0006] The martensitic stainless steel hot-rolled annealed steel sheet of the present invention is composed of, by weight, 0.14-0.21% C, 0.05-0.11% N, 0.1-0.6% Si, 0.4-1.2% Mn, 14.0-17.0% Cr, 0.2-0.32% C+N, with the remainder being Fe and unavoidable impurities, and has 25 particles / 100 μm in the microstructure. 2 The above chromium carbides or chromium nitrides are distributed, the precipitation temperature of the chromium carbides is 950° C. or lower, and the PREN value of the following formula (1) is 16 or higher. Formula (1) Cr+3.3Mo+16N (In the formula, Cr, Mo, and N represent the content (wt%) of each alloy element.)
[0007] The elongation of the hot-rolled annealed martensitic stainless steel sheet of the present invention may be 20% or more.
[0008] The highly corrosion-resistant martensitic stainless steel of the present invention contains, by weight, 0.14-0.21% C, 0.05-0.11% N, 0.1-0.6% Si, 0.4-1.2% Mn, 14.0-17.0% Cr, 0.2-0.32% C+N, with the remainder being Fe and unavoidable impurities, and is characterized in that the PREN value of the following formula (1) is 16 or more, and the value of the following formula (2) is 950 or less. Formula (1) Cr+3.3Mo+16N Formula (2)674+569C-4.17Si+0.46Mn+10.3Cr+193N (In the formula, Cr, Mo, N, C, Si, and Mn represent the content (wt%) of each alloy element.)
[0009] The highly corrosion-resistant martensitic stainless steel of the present invention may have a Rockwell hardness in the range of 47 to 53 HRC. The stainless steel preferably has a pitting potential of 180 mV or more in a 3.5% NaCl aqueous solution at 25°C.
[0010] The method for producing a highly corrosion-resistant martensitic stainless steel of the present invention includes the steps of hot rolling a slab containing, by weight, 0.14-0.21% C, 0.05-0.11% N, 0.1-0.6% Si, 0.4-1.2% Mn, 14.0-17.0% Cr, 0.2-0.32% C+N, and the remainder being Fe and unavoidable impurities, subjecting the hot rolled material to a batch annealing heat treatment, and subjecting the hot rolled annealed material to a strengthening heat treatment, the batch annealing heat treatment including a step of treating a first crack at a temperature range of 720-900°C for 5-25 hours and a step of treating a second crack at a temperature range of 500-700°C for 5-15 hours, and the hot rolled annealed material has a matrix structure of ferrite with a grain size of 25 grains / 100 μm. 2 The above-mentioned chromium carbides or chromium nitrides are distributed in the steel.
[0011] The batch annealing heat treatment may further include a step of treating a pre-crack at a temperature range of 400 to 600° C. for 5 to 15 hours before the step of treating the first crack. After the step of treating the preliminary cracks, the temperature may be increased at a rate of 40 to 200° C. / h until the step of treating the first cracks. After the step of treating the first cracks, the material is preferably cooled at a rate of 10° C. / h or more until the step of treating the second cracks.
[0012] The strengthening heat treatment may include austenizing at a temperature of 1,000° C. or more for 1 minute or more, and quenching at room temperature at a rate of 0.15° C. / s or more. The process may further include a step of deep freezing at a temperature of -50 to 150°C for 10 seconds to 5 minutes, and a step of tempering at a temperature of 400 to 600°C for 30 minutes to 2 hours. Effect of the Invention
[0013] According to the present invention, the martensitic stainless hot-rolled annealed steel sheet of the present invention can improve the workability by controlling the uniform distribution of fine chromium carbides in the microstructure. The highly corrosion-resistant martensitic stainless steel of the present invention can suppress the residual chromium carbide after strengthening heat treatment by lowering the carbide precipitation temperature, and thus can exhibit excellent corrosion resistance even without containing relatively high contents of chromium and carbon. It is also possible to provide a martensitic stainless steel having a hardness suitable for use in Western-style tableware. [Brief description of the drawings]
[0014] [Figure 1] 1 is a scanning electron microscope (SEM) photograph of chromium carbide in the microstructure of hot-rolled annealed steel sheet of steel type F. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of chromium carbide in a fine structure of hot-rolled annealed steel sheet of steel type B after strengthening heat treatment. [Diagram 3] This is a scanning electron microscope (SEM) photograph of chromium carbide in a fine structure of hot-rolled annealed steel sheet of type F after strengthening heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The martensitic stainless steel hot-rolled annealed steel sheet according to one embodiment of the present invention is composed of, by weight, C: 0.14-0.21%, N: 0.05-0.11%, Si: 0.1-0.6%, Mn: 0.4-1.2%, Cr: 14.0-17.0%, C+N: 0.2-0.32%, the remainder being Fe and unavoidable impurities, and has 25 particles / 100 μm in the microstructure. 2 The above chromium carbides or chromium nitrides are distributed, the precipitation temperature of the chromium carbides is 950° C. or lower, and the PREN value (pitting corrosion resistance index) of the following formula (1) is 16 or higher. Formula (1) Cr+3.3Mo+16N Here, Cr, Mo, and N represent the content (wt%) of each alloy element.
[0016] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. The present invention is not limited to the embodiments presented herein and may be embodied in other forms. In the drawings, parts that are not relevant to the description may be omitted in order to clarify the present invention, and the size of components may be somewhat exaggerated in order to facilitate understanding. Furthermore, when a part "comprises" a certain component, this does not mean excluding other components, but means that it may further include other components, unless otherwise specified. The singular expression includes the plural expression unless there is a clear exception in the context.
[0017] Martensitic stainless steels for cutlery, especially for Western tableware, are required to have high corrosion resistance and hardness. After hot rolling and annealing, fine chromium carbide and / or chromium nitride (hereinafter referred to as chromium carbonitride) are uniformly distributed in the ferrite matrix, and then quickly redissolved in the high-temperature austenite phase through strengthening heat treatment. At this time, since chromium carbonitride easily redissolves, the following conditions are required to ensure a martensite structure with excellent corrosion resistance.
[0018] First, fine chromium carbonitrides must be formed in the ferrite structure of the hot-rolled annealed material, and then the precipitation temperature must be lowered. In the case of conventional 420-series martensitic stainless steel, the precipitation temperature of chromium carbonitrides is increased by the addition of 0.3% or more of high carbon, and the grain boundary preferential precipitation and growth of chromium carbonitrides causes local precipitation of coarse chromium carbonitrides at grain boundaries, which reduces the re-solubilization rate into the austenite phase during strengthening heat treatment, resulting in a decrease in hardness and corrosion resistance. In addition, even when carbon is added in the range of 0.2 to 0.3%, the precipitation temperature of chromium carbonitrides is increased, and chromium carbonitrides cannot be completely decomposed unless heat treatment is performed at a higher temperature during strengthening heat treatment. As a result, the final manufacturer needs a lot of energy to increase the strengthening heat treatment temperature, which increases energy costs, or chromium carbonitrides remain due to the limit of the heating capacity of the heat treatment furnace. If chromium carbonitrides remain, the carbides may act as base points for corrosion, and the expected improvement in corrosion resistance may not be achieved even if a high chromium content is added.
[0019] Therefore, the present invention provides an alloy component system for a highly corrosion-resistant martensitic stainless steel that can uniformly distribute fine chromium carbonitrides in the matrix structure by establishing a batch annealing pattern, and improves corrosion resistance by controlling the precipitation temperature of chromium carbonitrides to a low level at which they can all be decomposed during strengthening heat treatment, thereby providing an appropriate hardness during strengthening heat treatment.
[0020] The martensitic stainless hot-rolled annealed steel sheet according to one embodiment of the present invention is composed of, by weight, C: 0.14-0.21%, N: 0.05-0.11%, Si: 0.1-0.6%, Mn: 0.4-1.2%, Cr: 14.0-17.0%, C+N: 0.2-0.32%, and the remainder being Fe and unavoidable impurities. The reasons for limiting the contents of the alloy composition will be specifically explained below. Unless otherwise specified, all of the component compositions below are in percent by weight.
[0021] The carbon (C) content is 0.14 to 0.21%. If the C content is low, the hardness may decrease after the strengthening heat treatment, making it difficult to ensure machinability and wear resistance, so in the present invention, C is preferably added in an amount of 0.14% or more. However, if the C content is excessive, if chromium carbonitrides are formed in excess, the precipitation temperature will increase and they will remain even after the strengthening heat treatment, not only reducing corrosion resistance but also causing the risk of forming coarse carbides in the annealed structure due to carbon segregation. For this reason, the upper limit of the C content in the present invention is limited to 0.21%. More preferably, it is in the range of 0.145 to 0.17%.
[0022] The nitrogen (N) content is 0.05-0.11%. N is an element added to improve both corrosion resistance and hardness, and has the advantage that it does not induce localized fine segregation and does not form coarse precipitates even when added instead of C. For this effect, N is preferably added at 0.05% or more, more preferably 0.08% or more in the present invention. If the N content is excessive, it may be difficult to control the composition system because it exceeds the limit of dissolution in molten steel during casting, and there is a risk of pinhole defects appearing on the surface. In addition, in the present invention, the martensitic stainless steel for Western tableware is not required to have a high hardness exceeding 53HRC in Rockwell hardness, but is required to have high gloss properties for aesthetics, so the upper limit of the N content is limited to 0.11%.
[0023] The silicon (Si) content is 0.1-0.6%. Silicon is an element that is essentially added for deoxidation. For this reason, in the present invention, it is preferable that 0.1% or more of silicon is added. However, if the silicon content is excessive, there is a problem that the pickling property is deteriorated and the brittleness is increased. For this reason, it is preferable that the upper limit of the silicon content in the present invention is limited to 0.6%.
[0024] The manganese (Mn) content is 0.4-1.2%. Mn is an element that is essentially added for deoxidation. In order to compensate for the austenite stability that decreases due to the reduction of the C and N contents and to ensure the N solid solubility limit, it is preferable to add 0.4% or more of Mn in the present invention. However, if the Mn content is excessive, there is a risk that the surface quality of the steel will deteriorate and it will become difficult to ensure hardness due to the formation of residual austenite in the final heat treated material. For this reason, in the present invention, the upper limit of the Mn content is preferably limited to 1.2%. More preferably, it is in the range of 0.8 to 1.1%.
[0025] The chromium (Cr) content is 14.0-17.0%. Cr is a typical element that improves the corrosion resistance of stainless steels and plays a role in increasing the limit of N solid solubility. In the present invention, 14.0% or more of Cr is added to ensure sufficient corrosion resistance. However, if the Cr content is excessive, there are problems in that the manufacturing cost increases, and fine segregation of Cr components in the structure increases, inducing local coarsening of chromium carbonitrides, thereby reducing the corrosion resistance and hardness of the steel material that has been heat-treated for strengthening. Therefore, in the present invention, the upper limit of the Cr content is limited to 17.0%, and preferably in the range of more than 14.5% and less than 15.5%.
[0026] The total carbon (C) and nitrogen (N) content is 0.2 to 0.32%. C and N are preferably added at 0.2% or more to ensure the hardness of the steel after the strengthening heat treatment, and 0.23% or more is preferable to ensure the number of carbonitrides. On the other hand, if the C+N content is excessive, the fraction of chromium carbonitrides distributed during batch annealing of the hot-rolled steel sheet may increase, resulting in a decrease in elongation, and therefore the upper limit of the C+N content is limited to 0.32% in the present invention. In addition, in the case of martensitic stainless steel for Western tableware, a high hardness exceeding HRC53 for general cutlery applications is not required, but high gloss characteristics are required to provide aesthetic appeal. In the manufacture of such high-gloss Western tableware, if the hardness after the strengthening heat treatment exceeds HRC53, the workability of the polishing work to produce the gloss is reduced, and surface defects such as wavy shapes are induced on the surface, resulting in a problem of reduced productivity. Therefore, in order to prevent excessive hardness and control the hardness to an appropriate range, the upper limit of the C+N content is limited to 0.28% or less.
[0027] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude them. The above impurities are known to anyone skilled in the normal manufacturing process, so all the contents of the impurities are not specifically mentioned in this specification. In addition to limiting the contents of the alloying elements to the above conditions, the relationships between the elements may be further limited as follows.
[0028] The martensitic stainless hot-rolled annealed steel sheet and the strengthening heat-treated martensitic stainless steel of the present invention have a pitting resistance equivalent number (PREN) value, as shown in the following formula (1), of 16 or more. Formula (1) Cr+3.3Mo+16N In addition to limiting the contents of the alloying elements to the above conditions, excellent corrosion resistance can be ensured by controlling the contents of the alloying elements so that the value of formula (1) is 16.5 or more.
[0029] A method for producing a martensitic stainless steel hot-rolled annealed steel sheet in which chromium carbonitrides are finely distributed before the strengthening heat treatment will be described. The martensitic stainless steel hot rolled material having the above alloy composition is produced as a slab by continuous casting or ingot casting, and then hot rolled to produce a hot rolled steel sheet that can be processed. The hot rolled steel sheet thus produced is then subjected to a batch annealing heat treatment to ensure good workability before processing such as precision rolling to a thickness that can be used for blades. The microstructure after the batch annealing heat treatment should be mainly ferrite with fine chromium carbides uniformly distributed. The martensitic stainless steel hot rolled annealed material is then produced as a martensitic stainless steel by a subsequent strengthening heat treatment step.
[0030] First, the batch annealing heat treatment will be described. The batch annealing heat treatment includes a step of treating the first crack, a step of treating the second crack, and may optionally further include a step of treating a pre-crack before the step of treating the first crack. The pre-crack treatment step is a step of treating cracks before the first crack treatment step, and is a pre-treatment step for uniformly increasing the temperature throughout the material. According to one example, the pre-crack treatment step is preferably performed by heating at a constant temperature in the range of 400 to 600°C for 5 to 10 hours. If the heating temperature is less than 400°C or exceeds 600°C, the temperature cannot be raised uniformly throughout the material, and if the heating time is less than 5 hours or exceeds 10 hours, the temperature cannot be raised uniformly throughout the material.
[0031] The step of treating the first cracks is a step of uniformly distributing chromium carbonitrides in the microstructure of the hot-rolled steel sheet. According to one example, the step of treating the first cracks is preferably performed by heating at a constant temperature of 720 to 900°C for 5 to 25 hours. When the heating temperature is less than 720°C, localized chromium carbonitride agglomerates are formed at the grain boundaries, whereas when the heating temperature exceeds 900°C, coarse chromium carbonitrides are formed at the grain boundaries. In addition, if the heating time is less than 5 hours, the size of the chromium carbonitrides can be refined, but the chromium carbonitrides may be distributed in a concentrated manner in one area. Conversely, if the heating time exceeds 25 hours, the chromium carbonitrides adjacent to each other may be mixed together and formed locally as coarse particles. Agglomerated or coarsely formed chromium carbides may cause material imbalance and reduce ductility, which may result in reduced rigidity, ductility, and corrosion resistance of the final product. To prevent this, the present invention limits the heating temperature in the step of treating the first cracks to 720 to 900°C and the heating time to 5 to 25 hours.
[0032] The step of treating the second cracks is a step of spheroidizing the chromium carbonitride. By spheroidizing the chromium carbonitride, it is possible to improve the workability in the subsequent processing steps. According to one example, the step of treating the second cracks is preferably performed by heating at a constant temperature in the temperature range of 500 to 700°C for 5 to 15 hours.
[0033] In order for the chromium carbonitrides to be spheroidized, a heating temperature of at least 500°C is required. On the other hand, if the heating temperature exceeds 700°C, the spheroidized chromium carbonitrides grow excessively, the number of pieces decreases, and the ductility decreases. Also, if the heating time is less than 5 hours, the chromium carbonitrides are not spheroidized, and if the heating time exceeds 15 hours, the chromium carbonitrides grow excessively and the ductility decreases.
[0034] After the step of treating the preliminary cracks, the temperature can be increased at a rate of 40 to 200° C. / h until the step of treating the first cracks. If the heating rate is less than 40°C / h, the time required to pass through the 700-750°C temperature range where chromium carbonitrides become coarse may increase, which may result in the size of the chromium carbonitrides becoming coarse and the number of chromium carbides distributed in the microstructure decreasing, resulting in a risk of reduced ductility. On the other hand, if the heating rate exceeds 200°C / h, the time required to pass through the temperature range where chromium carbonitrides become coarse decreases, ensuring fine chromium carbonitrides. However, there is a disadvantage in that the time for chromium carbonitrides to diffuse is insufficient, resulting in non-uniform distribution. After the step of treating the first cracks, the material may be cooled at a rate of 10° C. / h or more until the step of treating the second cracks. If the cooling rate is less than 10°C / h, the time spent passing through the temperature zone where the chromium carbonitrides coarsen increases, and as a result, the chromium carbonitrides in the microstructure coarsen, making it difficult to ensure high corrosion resistance and high hardness. After the second crack treatment step, air cooling is allowed.
[0035] In the batch annealing heat treatment step, carbon and chromium in the microstructure react to form chromium carbide, and nitrogen also reacts with chromium to form chromium nitride. As a result, the amount of carbon dissolved in the structure is reduced, improving workability, facilitating the subsequent stainless steel manufacturing process, and allowing processing into a desired final shape. The martensitic stainless hot-rolled annealed steel sheet according to an embodiment of the present invention may have an elongation rate of 20% or more. Chromium nitride also improves the hardness and corrosion resistance of the martensitic structure after quenching through a strengthening heat treatment. In addition, the chromium carbonitrides uniformly and finely distributed in the microstructure during the batch annealing heat treatment step enable rapid re-dissolution of carbon, nitrogen and chromium into the high-temperature austenite phase during the subsequent strengthening heat treatment step, thereby improving the hardness and corrosion resistance of the martensite structure after quenching.
[0036] According to the present invention, the chromium carbonitrides in the microstructure of the martensitic stainless steel hot-rolled annealed steel sheet can be refined and uniformly distributed through the above-mentioned batch annealing heat treatment, and the number of chromium carbonitrides in the microstructure can be reduced to 25 / 100 μm. 2 More than 25 chromium carbonitrides / 100μm are distributed in the microstructure. 2 If chromium carbonitrides are distributed below this range, the number of chromium carbonitrides will be small and the size will be coarse, resulting in reduced ductility and making it difficult for chromium and carbon to re-dissolve in the subsequent strengthening heat treatment step, making it impossible to ensure the desired hardness.
[0037] According to the present invention, the martensitic stainless steel hot-rolled and annealed product that has been subjected to the batch annealing heat treatment can be manufactured into a martensitic stainless steel through a step of working it into a final shape and then subjecting it to a strengthening heat treatment. The strengthening heat treatment may include an austenizing step and a quenching step, and may further include a deep freezing step and a tempering step as required.
[0038] The austenizing treatment is a step in which the base structure of the steel material is transformed from ferrite to austenite. In this step, the chromium carbonitride is redissolved as a matrix structure in the form of chromium, carbon, and nitrogen, and the hardness of the martensitic stainless steel can be increased after the subsequent quenching or deep freezing step.
[0039] According to one example, the austenizing step may be heat treated at a temperature of 1,000° C. or more for 1 minute or more. 23 Although the precipitation temperature of chromium carbide targeted by the present invention is 950°C or lower, depending on the alloy component composition. The precipitation temperature of chromium carbide can be changed by the alloy component composition and can be expressed by the following formula (2). As can be seen from formula (2), the precipitation temperature of chromium carbide becomes higher as the chromium and carbon contents become higher. Formula (2)674+569C-4.17Si+0.46Mn+10.3Cr+193N
[0040] When a large amount of chromium is added to improve corrosion resistance, or when a large amount of carbon and nitrogen is added to improve hardness, the precipitation temperature of chromium carbide becomes high, and the austenizing temperature range of the strengthening heat treatment is restricted. As described above, if all of the chromium carbide is not redissolved and remains due to equipment problems caused by limited heating capacity or problems of increased energy costs during the actual strengthening heat treatment, the corrosion resistance is rather reduced. Therefore, in the present invention, the precipitation temperature of chromium carbide is limited to 950°C or less along with the alloy composition so that the total amount of added chromium and carbon contributes to corrosion resistance.
[0041] If the austenizing temperature is less than 1,000°C, it becomes difficult to completely decompose the chromium carbides, and the treatment time becomes long, which is uneconomical.On the other hand, if the treatment temperature is too high, the energy cost increases, which is uneconomical, and there is a risk of the hardness decreasing due to the excessive formation of retained austenite caused by the increase in the amount of re-dissolved carbides, and the crystal grains grow excessively, so it is preferable to limit the temperature to 1,200°C or less. Furthermore, if the austenizing treatment time is less than 1 minute, it is difficult to completely decompose the chromium carbide, and the desired hardness cannot be obtained. If the treatment time is longer, there is a risk that the crystal grains will grow excessively and residual austenite will be generated. Therefore, it is preferable to limit the treatment time to 30 minutes or less.
[0042] The quenching step is a step in which the austenitic structure is transformed into hard martensite by rapidly cooling to room temperature at a cooling rate of 0.15℃ / s or more after the austenizing treatment. If the cooling rate is 0.2℃ / s or more, a higher martensite hardness can be obtained. The deep freezing step is a step of further cooling the steel material quenched at room temperature to an extremely low temperature to further transform the residual austenite structure into a martensite structure, and the hardness of the steel material is further increased in this step. According to one example, the deep freezing step may be a subzero heat treatment at a temperature of -50 to -150°C for 10 seconds to 5 minutes.
[0043] The tempering step is a step for imparting toughness to the martensite structure, which is hard and brittle, after the deep freezing step. According to one example, the heat treatment can be performed at a temperature of 400 to 600° C. for 30 minutes to 2 hours.
[0044] According to the present invention, the ferrite structure may be finally transformed into a martensite structure during the strengthening heat treatment, thereby ensuring the desired hardness and high corrosion resistance. For example, after redissolution by the strengthening heat treatment, the area fraction of chromium carbonitride remaining in the cross section of the material is preferably 2% or less. The highly corrosion-resistant martensitic stainless steel according to an embodiment of the present invention preferably has a pitting potential of 180 mV or more in a 3.5% NaCl aqueous solution at 25° C. This can be ensured by controlling the PREN value of the above formula (1) to 16.0 or more and the precipitation temperature of chromium carbide to 950° C. or less to re-dissolve all the carbide. Furthermore, the highly corrosion-resistant martensitic stainless steel according to one embodiment of the present invention preferably has a Rockwell hardness of 47 to 53 HRC.
[0045] Among martensitic stainless steels for cutlery, those for Western tableware do not require high hardness, and polishing for luster can cause problems in work productivity, so a hardness of more than 53HRC is not required. For Western tableware knives, the appropriate hardness range is 49-53HRC for the blade and 47-51HRC for the handle. Therefore, in the present invention, the upper limit of the C+N content is limited to 0.32% or less, and the alloy composition is limited to the above range so that the appropriate hardness is obtained even if the entire amount is redissolved through control of the precipitation temperature of chromium carbide. Therefore, the highly corrosion-resistant martensitic stainless steel of the present invention preferably has a Rockwell hardness range of 47-53HRC.
[0046] The present invention will now be described in more detail with reference to preferred embodiments thereof. [Example] The alloy components shown in Table 1 below were cast, hot rolled, and then batch annealed. The batch annealing was performed by treating the pre-crack at 500°C for 7 hours, increasing the temperature at a rate of about 100°C / h to 840°C for 10 hours to treat the first crack, cooling at a rate of 15°C / h, maintaining at 580°C for 10 hours, and then air cooling.
[0047] [Table 1]
[0048] In Table 1, the precipitation temperature (° C.) of chromium carbonitride and the presence or absence of pinholes caused by nitrogen gas on the surface of the material are indicated by ○ or ×. Steel B contained a large amount of N outside the range of the present invention, which caused pinholes to form on the surface, and steel E contained an appropriate N content but a low Cr content that affects the nitrogen solid solubility, and also contained relatively low contents of C and Mn, which are austenite stabilizing elements, causing N beyond the solid solubility limit to form gas and generate pinholes. Steel F, which falls within the alloy composition range of the present invention, did not generate pinholes due to nitrogen gas, and had a low precipitation temperature of chromium carbide of 937°C, which worked advantageously during the strengthening heat treatment described below.
[0049] In addition, when the C and Cr contents are high, the precipitation temperature of chromium carbide is 990°C or higher, but when the entire alloy composition range including C and Cr falls within the range of the present invention, it was confirmed that the precipitation temperature is 950°C or lower. The number of chromium carbonitrides in the microstructure of the hot-rolled annealed materials A to F produced as described above was observed using a scanning electron microscope (SEM), and tensile tests were conducted according to the JIS 13B standard to obtain the elongation percentages, which are shown in Table 2 below.
[0050] [Table 2]
[0051] Referring to Table 2, steel type A contains 0.6% or more C and has 60 chromium carbonitrides per 100 μm. 2Although a large amount of the above was observed, it was found that the elongation rate was extremely poor at 17.6%. Steel types B and C both have a high C content of about 0.25%, but there is a difference in N content. Steel type B has a higher C+N content, but has a lower number of particles per 100μm than steel type C, at 21 particles per 100μm. 2 The number of carbonitrides in steel type B is 32 / 100μm, which is presumably due to the high distribution of precipitated chromium carbonitrides, causing them to become coarse. Steel type B also had a high C+N content and was slightly inferior in elongation at 19.6%. Steel type C had a distribution of chromium carbonitrides of 32 / 100μm. 2 , and the elongation rate is good at 29.3%, but the precipitation temperature of chromium carbide is high at 991°C, and there is a high possibility that chromium carbonitride remains after strengthening heat treatment. In the case of steel types D and E, the elongation rate was measured as good at 28% or more, but the number of chromium carbonitrides was 25 / 100μm. 2 This was presumably because the C+N content was appropriate but the Cr content was low.
[0052] Fig. 1 is a scanning electron microscope (SEM) photograph of chromium carbonitrides in the microstructure of hot-rolled annealed steel sheet of steel grade F. It can be seen that the hot-rolled annealed steel sheet of steel grade F, which corresponds to the inventive steel of the present invention, has fine chromium carbonitrides uniformly distributed in the ferrite matrix structure, with an average particle size of 30 particles / 100 μm as shown in Table 2. 2 It showed a standard distribution of chromium carbonitrides and the elongation was measured to be excellent at 30.2%.
[0053] The martensitic stainless steel hot-rolled and annealed material was then austenized at 1,050°C and quenched at a cooling rate of 0.27°C / s to produce martensitic steel. Table 3 below shows the PREN and pitting potential measurements to determine corrosion resistance, and the Rockwell hardness was measured to determine hardness. The PREN value was calculated by substituting the content (weight%) of each alloy element into formula (1), and the pitting potential was measured in a 3.5% NaCl aqueous solution at 25°C.
[0054] [Table 3]
[0055] Steel type A, which contains 0.6% or more of high carbon, showed the lowest pitting corrosion potential due to the sensitization phenomenon caused by Cr deficiency and the high precipitation temperature of chromium carbide, which resulted in the residual chromium carbonitride. In the case of steel type B, in which nitrogen was added above its solid solubility limit, causing nitrogen gas pinholes, the effect of N showed the highest PREN value and pitting potential, but the occurrence of surface pinholes made it unsuitable for use in products. Steel type C showed a PREN value of 17.21 and a high pitting potential of 212 mV, but had a high C content and a high hardness of 54.7 HRC, which exceeded the appropriate hardness range of 47 to 53 HRC for preventing surface defects during polishing for gloss as described above.
[0056] In the case of steels D and E, the Cr and N contents were similar, and they showed similar pitting potential values around 95 mV and similar hardness values. Steel type F, which corresponds to the steel of the present invention, showed a PREN value of 16.52, which is equal to or greater than 16.0, an excellent pitting potential value of 199 mV, and a hardness value of 51.4 HRC, which is at an appropriate level.
[0057] Figures 2 and 3 are scanning electron microscope (SEM) images of chromium carbide in the microstructure after strengthening heat treatment of hot-rolled annealed steel sheets of steel type B and steel type F. It can be seen that steel type B shown in Figure 2 is unable to distribute chromium carbonitrides uniformly in the hot-rolled annealed material due to the high C+N content, and is coarsened and segregated, and the precipitation temperature of chromium carbide is also high, so it is not redissolved even after strengthening heat treatment and remains. On the other hand, it can be seen that in steel type F, the inventive steel, most of the chromium carbonitrides are redissolved after strengthening heat treatment through control of the C+N and Cr contents and the precipitation temperature of chromium carbide, and the area fraction of chromium carbonitride remaining in the cross section meets the requirement of 2% or less.
[0058] As described above, exemplary embodiments of the present invention have been described, but the present invention is not limited thereto, and a person having ordinary skill in the art will understand that various changes and modifications are possible within the scope of the concept and scope of the claims described below. [Industrial Applicability]
[0059] The martensitic stainless steel according to the present invention has improved corrosion resistance and can ensure appropriate hardness during strengthening heat treatment, making it suitable for use as a material for Western-style tableware.
Claims
1. In weight percent, C: 0.14-0.21%, N: 0.05-0.11%, Si: 0.1-0.6%, Mn: 0.4-1.2%, Cr: 14.0-17.0%, C+N: 0.2-0.32%, and the remainder is Fe and unavoidable impurities. 25 / 100μm in the microstructure 2 The above chromium carbides and / or chromium nitrides are distributed, The precipitation temperature of the chromium carbide is 950° C. or less, The PREN value (pitting corrosion resistance index) of the following formula (1) is 16 or more, A highly corrosion-resistant martensitic stainless hot-rolled annealed steel sheet, characterized in that the value of the following formula (2) is 950 or less: Formula (1) Cr+3.3Mo+16N Formula (2) 674+569C-4.17Si+0.46Mn+10.3Cr+193N (Here, Cr, Mo, N, C, Si, and Mn mean the content (wt%) of each alloy element.)
2. 2. The highly corrosion-resistant martensitic stainless hot-rolled annealed steel sheet according to claim 1, characterized in that the elongation is 20% or more.
3. In weight percent, C: 0.14-0.21%, N: 0.05-0.11%, Si: 0.1-0.6%, Mn: 0.4-1.2%, Cr: 14.0-17.0%, C+N: 0.2-0.32%, and the remainder is Fe and unavoidable impurities. The PREN value (pitting corrosion resistance index) of the following formula (1) is 16 or more, A highly corrosion-resistant martensitic stainless steel sheet, characterized in that the value of the following formula (2) is 950 or less: Formula (1) Cr+3.3Mo+16N Formula (2) 674+569C-4.17Si+0.46Mn+10.3Cr+193N (Here, Cr, Mo, N, C, Si, and Mn mean the content (wt%) of each alloy element.)
4. 4. The highly corrosion-resistant martensitic stainless steel sheet according to claim 3, characterized in that the Rockwell hardness is in the range of 47 to 53 HRC.
5. 4. The highly corrosion-resistant martensitic stainless steel sheet according to claim 3, characterized in that the pitting potential is 180 mV or more in a 3.5% NaCl aqueous solution at 25°C.
6. A method for producing a highly corrosion-resistant martensitic stainless steel sheet, comprising the steps of hot rolling a slab containing, by weight, 0.14-0.21% C, 0.05-0.11% N, 0.1-0.6% Si, 0.4-1.2% Mn, 14.0-17.0% Cr, 0.2-0.32% C+N, and the remainder being Fe and unavoidable impurities; subjecting the hot rolled material to a batch annealing heat treatment; and subjecting the hot-rolled annealed material to a strengthening heat treatment, The batch annealing heat treatment includes a step of uniformly distributing chromium carbonitride in the microstructure of the hot-rolled steel sheet at a temperature range of 720 to 900° C. for 5 to 25 hours, and a step of spheroidizing the chromium carbonitride at a temperature range of 500 to 700° C. for 5 to 15 hours, In the batch annealing heat treatment, a pretreatment step for uniformly increasing the temperature over the entire material is performed in a temperature range of 400 to 600 ° C. for 5 to 10 hours before the step of uniformly distributing chromium carbonitride in the microstructure of the hot-rolled steel sheet, The temperature is increased at a rate of 40 to 200° C. / h until the chromium carbonitride is uniformly distributed. After the step of uniformly distributing the chromium carbonitride, the chromium carbonitride is cooled at a rate of 10° C. / h or more until the step of spheroidizing the chromium carbonitride; The strengthening heat treatment includes austenizing at a temperature of 1,000° C. or more for 1 minute or more, and rapidly cooling to room temperature at a cooling rate of 0.15° C. / s or more, and quenching. The strengthened heat-treated hot-rolled annealed material has a ferrite matrix structure with a particle size of 25 particles / 100 μm. 2 The above chromium carbides and / or chromium nitrides are distributed, A method for producing a highly corrosion-resistant martensitic stainless steel sheet, characterized in that the PREN value (pitting corrosion resistance index) of the following formula (1) is 16 or more, and the value of the following formula (2) is 950 or less. Formula (1) Cr+3.3Mo+16N Formula (2) 674+569C-4.17Si+0.46Mn+10.3Cr+193N (Here, Cr, Mo, N, C, Si, and Mn mean the content (wt%) of each alloy element.)
7. 7. The method of claim 6, further comprising the steps of: performing deep cooling at a temperature of -50 to -150°C for 10 seconds to 5 minutes, and tempering at a temperature of 400 to 600°C for 30 minutes to 2 hours, after the quenching step.
Citation Information
Patent Citations
Process for producing rust proofing* medium carbon* martensitic* chrom ium stainless steel
JP1977007818A
Martensitic stainless steel having no pinhole defect and its production method
JP2005163176A
Martensitic stainless steel excellent in corrosion resistance
JP2008163452A
Martensitic stainless steel having excellent corrosion resistance
JP2010215995A